2007
DOI: 10.1128/cvi.00299-07
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protein Antigens for Early Serological Diagnosis of Leprosy

Abstract: Leprosy is a chronic and debilitating human disease caused by infection with the Mycobacterium leprae bacillus. Despite the marked reduction in the number of registered worldwide leprosy cases as a result of the widespread use of multidrug therapy, the number of new cases detected each year remains relatively stable. This indicates that M. leprae is still being transmitted and that, without earlier diagnosis, M. leprae infection will continue to pose a health problem. Current diagnostic techniques, based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 17 publications
5
139
2
10
Order By: Relevance
“…The risk factors identified in this study include contact with cases of PB leprosy with two-five lesions or MB disease, physical closeness, such as residing within the sponses to LID-1 up to one year prior to the development of clinical symptoms. These antibody titres were higher and occurred much sooner than the increases in the anti-PGL-I IgM responses observed in the same individuals (Duthie et al 2007). It was also shown that a heightened IgG titre against LID-1 was a good indicator of early infection and active disease, as titres remained low or undetectable in contacts who did not progress to disease.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The risk factors identified in this study include contact with cases of PB leprosy with two-five lesions or MB disease, physical closeness, such as residing within the sponses to LID-1 up to one year prior to the development of clinical symptoms. These antibody titres were higher and occurred much sooner than the increases in the anti-PGL-I IgM responses observed in the same individuals (Duthie et al 2007). It was also shown that a heightened IgG titre against LID-1 was a good indicator of early infection and active disease, as titres remained low or undetectable in contacts who did not progress to disease.…”
Section: Discussionmentioning
confidence: 81%
“…The reactivities of the antibodies in the baseline samples against three key antigens, including LID-1 (which had been shown in a previous study to elicit a positive antibody response in individuals who were diagnosed with clinical leprosy up to one year prior to the onset of disease symptoms) (Duthie et al 2007), ML2028 (Ag85B) and native MLSA, which was examined to assess reactivity against LAM, were determined by Western blot analysis, as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Duthie et al [173], focused on the search for potential serologically reactive protein antigens prior to testing for the rigorous requirement for leprosy specifi city when tested in various endemic populations. Such approaches lead to the identifi cation of new antigens (ML0405, ML 2331) from which novel fusion proteins were designed.…”
Section: Defi Ning Mycobacterium Leprae Tnmentioning
confidence: 99%